Disseminated Tuberculosis Presenting as Baker's Cyst Infection. (10th January 2017) - Pervin, Najwa; Akram, Sami; Hudali, Tamer; Bhattarai, Mukul; Waqar, Sana
Abstract : In the absence of coexisting immunocompromised state and lack of specific symptoms a reactivation of treated mycobacterial tuberculosis (MTB) infection is generally not considered in the differential diagnosis of leg pain. We present a unique case of disseminated tuberculosis presenting as an infected Baker's cyst in a 73-year-old immunocompetent male.